Diagnostic efficacy of rapid assays used for the detection of hepatitis B virus surface antigen - EWS Chameera; F Noordeen; H Pandithasundara; AMSB Abeykoon (Sri Lankan Journal of Infectious Diseases, 2013)
Objectives: Two rapid tests, CORTEZ’S HBsAg one step and CTK Biotech’s Onsite HBsAg, for the detection of HBsAg in the serum were compared using the SURASE B-96 (TMB) enzyme immunoassay (EIA) as the comparator. Methods: Fifty blood samples (n=50) were tested using the two rapid tests and the EIA. Results: Based on the EIA, 5 sera were positive for HBsAg and 45 sera were negative for HBsAg. However, 4 sera were positive while 46 sera were negative for HBsAg when tested by Biotech’s Onsite HBsAg. Three (n=3) sera were positive while 47 sera were negative for HBsAg when tested by CORTEZ’S HBsAg one step detection kit. The specificity and the positive predictive value (PPV) were 100% for both rapid tests. However, the sensitivity and negative predictive value (NPV) for Biotech’s Onsite HBsAg assay and CORTEZ’S HBsAg one step assay were 80% and 97.82% and 60% and 95.74%, respectively. Conclusions: Both rapid tests showed less sensitivity and NPV than the EIA. Sensitivity and NPV were higher with Onsite HBsAg than the CORTEZ’S HBsAg making the former slightly better than the latter for detecting serum HBsAg. According to our findings, the accuracy of rapid tests for HBsAg detection varied compared to EIA, suggesting the importance of validating rapid tests routinely when used in diagnostic laboratories. DOI: http://dx.doi.org/10.4038/sljid.v3i2.5172 Sri Lankan Journal of Infectious Diseases 2013; Vol.3(2):21-27